2019
DOI: 10.3126/jbpkihs.v2i1.24972
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use and Dependence among Psychiatry Out-Patients of a Health Institute in Eastern Nepal

Abstract: Background: Assessment of nicotine dependence among tobacco users is essential as highly dependent individuals have greater risk of developing tobacco related physical and psychiatric problems. There is little information about the tobacco use and nicotine dependence among psychiatric patients in developing countries, including Nepal. Objectives: To estimate the prevalence of tobacco use, the level of nicotine dependence and the psychiatric disorder specific prevalence among tobacco users visiting a psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
1
3
1
Order By: Relevance
“…This prevalence points towards the extent of the problem in this part of the world. 17,18 A study conducted by Josseran et al 20 in a Paris medical school showed that more than one third of students were smokers (35%); 21% were daily smokers and 14% were occasional smokers which is comparable to this study. Budhathoki N et al 9 have studied substance use among third year Medical students of Nepal and found that about 56.20% of the students used tobacco after joining medical school in comparison to 43.80% consumed tobacco before joining medical school and majority of them were in hostels (53%) and rented house (62.50%).…”
Section: Association Of Cannabis With Socio Demographic Profilesupporting
confidence: 87%
See 1 more Smart Citation
“…This prevalence points towards the extent of the problem in this part of the world. 17,18 A study conducted by Josseran et al 20 in a Paris medical school showed that more than one third of students were smokers (35%); 21% were daily smokers and 14% were occasional smokers which is comparable to this study. Budhathoki N et al 9 have studied substance use among third year Medical students of Nepal and found that about 56.20% of the students used tobacco after joining medical school in comparison to 43.80% consumed tobacco before joining medical school and majority of them were in hostels (53%) and rented house (62.50%).…”
Section: Association Of Cannabis With Socio Demographic Profilesupporting
confidence: 87%
“…Nicotine use doesn't appear to be lower than general population in this region. A study conducted at the department of Psychiatry by Limbu et al reveals that the prevalence of tobacco use was 55.6% in OPD, 17 62.2% in admitted 18 cases and 41.4% in community 19 . Tobacco use was more common among males in all three settings (p value < 0.05).…”
Section: Association Of Cannabis With Socio Demographic Profilementioning
confidence: 99%
“…Studies have identified that hormonal, cultural, and behavioural factors are linked with the differences in smoking among males and females. (14) A study done on the depressive patients in Tribhuwan University Teaching Hospital (TUTH), Nepal, (6) and another study done in the psychiatric outpatient department of BP Koirala Institute of Health Science (5) found that 37.2% and 38% of patients are current smokers, respectively which is higher than that of our study's finding. However, the study participants in those studies comprised a higher number of male patients which may have increased the overall prevalence of smoking in those studies.…”
contrasting
confidence: 80%
“…Where, n= minimum required sample size z= 1.96 at 95% Confidence Interval (CI) p= prevalence taken as 38% from the previous study (5) q= 1-p e= margin of error, 5%…”
mentioning
confidence: 99%
See 1 more Smart Citation